Ionization-Induced Subcycle Metallization of Nanoparticles in Few-Cycle Pulses - Liu, Qingcao; Seiffert, Lennart; Suessmann, Frederik; Zherebtsov, Sergey; Passig, Johannes; Kessel, Alexander; Trushin, Sergei A.; Kling, Nora G.; Ben-Itzhak, Itzik; Mondes, Valerie; Graf, Christina; Ruehl, Eckart; et al. (ACS Photonics, 2020)
Strong-field laser-matter interactions in nanoscale targets offer unique avenues for the generation and detailed characterization of matter under extreme conditions. Field-driven, subcycle ionization-induced metallization of nanoscale solids in intense laser fields has been predicted (Peltz et al. Time-Resolved X-ray Imaging of Anisotropic Nanoplasma Expansion. Phys. Rev. Lett. 2014, 113, 133401), but its observation was hampered by a lack of a smoking gun. Here, we report the ultrafast metallization of isolated dielectric and semiconducting nanoparticles under intense few-cycle laser pulses. The highest-energy electron emission is found to be a decisive proof that shows a characteristic cutoff modification to a metallic limit for intensities high enough to ignite carrier avalanching in the volume of the particles. Semiclassical Mean-field Mie Monte-Carlo transport simulations reveal the underlying dynamics and explain the observed evolution by near-field driven electron backscattering from the metallizing target.
CRIS-Team Scopus Importer:2023-04-20
Keywords: avalanche ionization; strong-field nanophysics